Demonstration of allelopathy of horseradish root extract on lettuce seed. Issue 3 (12th February 2019) - Simpson, Tyler; Chiu, Yu‐Chun; Richards‐Babb, Michelle; Blythe, Jessica M.; Ku, Kang‐Mo
Abstract: Allelopathy plays crucial roles in invasive plant viability and agricultural production systems. However, there is no well‐established hands‐on learning activity to teach the concept of allelopathy. Nor is there an activity which allows students to gain knowledge about glucosinolates and their corresponding enzyme, myrosinase, which are present in almost all Brassica crops. Lettuce germination was counted by the students from three different treatments including water treated with Parafilm sealing, horseradish treated with Parafilm sealing, and horseradish treated without Parafilm sealing. Additionally, lettuce root length was measured by students using ImageJ software from each treatment using pictures captured by students' smartphones. Students took an identical quiz as a pre‐laboratory and a post‐laboratory assignment. Their average scores on the pre‐laboratory and post‐laboratory quizzes were 3.14 and 6.56 out of 10, respectively, indicating the lab activity significantly improved students' understanding of allelopathy and glucosinolate‐myrosinase system. In addition, students ( n = 76) completed a survey post‐laboratory to assess their self‐efficacy. This simple and cost‐effective laboratory activity improved students' knowledge and skill development as it made learning more inviting, meaningful, and fun. © 2019 International Union of Biochemistry and Molecular Biology, 47(3):333–340, 2019.